Phosphatidylethanolamine in Trypanosoma brucei Is Organized in Two Separate Pools and Is Synthesized Exclusively by the Kennedy Pathway - Signorell, Aita (American Society for Biochemistry and Molecular Biology, 2008)
Phosphatidylethanolamine is a major phospholipid class of all eukaryotic cells. It can be synthesized via the CDP-ethanolamine branch of the Kennedy pathway, by decarboxylation of phosphatidylserine, or by base exchange with phosphatidylserine. The contributions of these pathways to total phosphatidylethanolamine synthesis have remained unclear. Although Trypanosoma brucei, the causative agent of human and animal trypanosomiasis, has served as a model organism to elucidate the entire reaction sequence for glycosylphosphatidylinositol biosynthesis, the pathways for the synthesis of the major phospholipid classes have received little attention. We now show that disruption of the CDP-ethanolamine branch of the Kennedy pathway using RNA interference results in dramatic changes in phosphatidylethanolamine, phosphatidylserine, and phosphatidylcholine. By targeting individual enzymes of the pathway, we demonstrate that de novo phosphatidylethanolamine synthesis in T. brucei procyclic forms is strictly dependent on the CDP-ethanolamine route. Interestingly, the last step in the Kennedy pathway can be mediated by two separate activities leading to two distinct pools of phosphatidylethanolamine, consisting of predominantly alk-1-enyl-acyl- or diacyl-type molecular species. In addition, we show that phosphatidylserine in T. brucei procyclic forms is synthesized exclusively by base exchange with phosphatidylethanolamine.